Public awareness over the purchase of usury-free cars. Case study among SMK Pekan Baru staff / Nur Adibah Azmi - Azmi, Nur Adibah (2021)
The lack of knowledge is a major factor by Muslims today involved in the element of Riba’ (usury). There are various discussions that have been discussed by scholars' earlier in his classic books and have also been discussed by academics in his academic field. However, there are many people still take and use Riba’ in their lives. Riba’ has also become a habit for people nowadays to use it when they want to do any transaction related to trading or debts. Meanwhile, in this era of globalization, cars have become an important thing among the community to continue their lives. The connection of a car with Riba’ is when there is an increase of money in the transaction. This caused the occurs of Riba’ in buying and selling. Most people are unaware because they are not exposed to the knowledge of the prohibition of Riba’ which belongs to the great sins. They are as normal human beings, only see the debts due when buying the car is just custom. They do not realize that, if they do not take the Islamic transactions, the tendency to engage with Riba’ is very high. Therefore, this study is to identify the awareness of teachers in SMK Pekan Baru over the purchase of usury-free cars. This study is based on the information received from interviews and questionnaires on the concerns of teachers when wanting to buy a car without Riba’. The information obtained was analysed to identify the level of awareness among teachers at SMK Pekan Baru on the purchase of a usury-free cars. Thus, the discussions related to the teachers’ awareness over the purchase of usury-free cars have been discussed clearly and well. It is a hope that this study can give awareness to the community about the prohibition of Riba’ in the purchase of cars.